Pengaruh Pemberian Pupuk NPK Mutiara dan Pupuk Kascing Terhadap Pertumbuhan dan Hasil Tanaman Okra Merah (Abelmoschus esculetus (L) Moench) - Nasution, Khairul Aswat; Susanti, Rini (JURNAL AGROPLASMA, 2025)
The aim of the research was to determine the effect of NPK pearl fertilizer and vermicompost fertilizer on the growth and yield of red okra plants. (Abelmoschus esculetus (L) Moench) This study used a factorial Randomized Group Design (RAK) with 2 treatment factors. The first factor was the application of NPK pearl fertilizer (N) consisting of four levels, N0: Control, N1: 15 g/polybag, N2: 30 g/polybag, N3: 45 g/polybag. The second factor was the application of vermicompost fertilizer (K) which consists of four levels, K0: Control, K1: 90 g/polybag, K2: 120 g/polybag, K3: 150 g/polybag. The parameters measured were plant height, stem diameter, number of branches, number of fruit per plant, number of fruit per plot, wet weight of fruit per plant, leaf chlorophyll content. Based on observation data from the Duncan’s Multiple Range Test (DMRT) analysis, the application of NPK Mutiara fertilizer showed a significant effect on plant height, stem diameter, number of branches, number of fruits per plant, number of fruits per plot, and fresh fruit weight per plant, with the best result observed at a dosage of 45 g/polybag (N3). The application of kascing fertilizer had a significant effect on all observed parameters, with the best result at 150 g/polybag (K3). The interaction between NPK Mutiara fertilizer and kascing fertilizer did not show a significant effect on any of the measured parameters. Keywords: pearl NPK fertilizer, vermicompost fertilizer, red okra